When is nonfundamentalness in SVARs a real problem? - Paul Beaudry; Patrick Fève; Alain Guay; Franck Portier (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
In SVARs, identification of structural shocks can be subject to nonfundamentalness, as the econometrician may have an information set smaller than the economic agents' one. How serious is that problem from a quantitative point of view? In this paper we propose a simple diagnostic for the quantitative importance of nonfundamentalness in structural VARs. The diagnostic is of interest as nonfundamentalness is not an either/or question, and its quantitative implications can be more or less severe. As an illustration, we apply our diagnostic to the identification of TFP news shocks and we find that nonfundamentalness is of little quantitatively importance in that context.
Keywords: C32; E32; 330; NonFundamentalness; Business Cycles; SVARs; News Shocks